The Czech version of the life satisfaction index for the third age-short form (LSITA-SF12): Psychometric properties - Bužgová, Radka; Bobčíková, Katka; Kozáková, Radka; Zeleníková, Renáta (International journal of older people nursing, 2023)
BACKGROUND: Evaluation of life satisfaction of older people using standardised tools can play a crucial role in evaluating the effectiveness of policy measures aimed at mitigating the effects of population aging. OBJECTIVES: The aim of the study was to verify the psychometric properties of the Czech version of a 12-item scale (the Life Satisfaction Index for the Third Age) for older people living in the community. METHODS: The research involved 1113 older people from the Moravian-Silesian Region over 60 years of age living in a home environment. For the newly created Czech version of LSITA-SF12, we tested validity (construct validity and convergent validity) and reliability (internal consistency). RESULTS: We confirmed a single-factor model for the LSITA-SF12 scale (χ2 = 71.33, p < .001, CFI = 0.995, TLI = 0.994, RMSEA = 0.065, SRMR = 0.056, GFI = 0.999) by confirmatory factor analysis and load factor analysis (values of explorations ≥0.45). The internal consistency of the scale was satisfactory (α = 0.878). Furthermore, there was a medium correlation rate (r = 0.592; p < .001) between the overall score of the LSITA-SF and quality-of-life score (OPQoL-Brief). CONCLUSIONS: We found the Czech version of the LSITA-SF12 questionnaire to have satisfactory psychometric properties. The questionnaire is suitable for use in research and clinical practice to evaluate the effectiveness of preventive measures. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov. PRS Protocol Registration and Results System; NCT05637177. IMPLICATION FOR PRACTICE: The LSITA_SF12 questionnaire can beadministered by a community gerontological nurse and can be used in clinicalpractice and research.
Keywords: reprodukovatelnost výsledků; Personal Satisfaction; Czech Republic; lidé; osobní uspokojení; Reproducibility of Results; průzkumy a dotazníky; Humans; Aged; Psychometrics; senioři; Quality of Life; lidé středního věku; Surveys and Questionnaires; Česká republika; Middle Aged; psychometrie; kvalita života